A novel gene signature related to focal adhesions for distinguishing and predicting the prognosis of lung squamous cell carcinoma - Hui, Gang; Xie, Yuancai; Niu, Li; Liu, Jixian (Frontiers in Medicine, 2024)
Background: Lung squamous cell carcinoma (LUSC) is a devastating and difficult-to-treat type of lung cancer, and the prognosis of LUSC is the worst. The functional roles of focal adhesion-related genes were explored in LUSC based on data from The Cancer Genome Atlas (TCGA). Methods: RNA sequencing data and clinical characteristics of LUSC patients in TCGA-LUSC were obtained from TCGA database. Through systematic analysis, we screened the prognostic genes and determined the focal adhesion-related pathways closely associated with LUSC.Results: We identified 444 prognostic genes and focal adhesion-related pathways intimately associated with LUSC. According to the focal adhesion-related genes, TCGA-LUSC patients were well divided into two groups: the low-risk group (G1) and the high-risk group (G2). A differential expression analysis identified 44 differentially expressed genes (DEGs) upregulated in the low-risk G1 group and 379 DEGs upregulated in the high-risk G2 group. The upregulated DEGs in the G1 group were primarily related to tyrosine metabolism, steroid hormone biosynthesis, retinol metabolism, platinum drug resistance, pentose and glucuronate interconversions, and metabolism of xenobiotics by cytochrome P450, while the downregulated DEGs in the G1 group were primarily related to ECM-receptor interaction, focal adhesion, proteoglycans in cancer, small cell lung cancer, cytokine-cytokine receptor interaction and TGF-beta signaling pathway. The immune activity of G1 group was lower than that of G2 group, and half-maximal inhibitory concentration (IC50) of 5 chemotherapy drugs (i.e., gemcitabine, methotrexate, vinorelbine, paclitaxel and cisplatin) were significantly different between G1 and G2 group. Furthermore, a 10-gene prognostic model was constructed to predict the prognosis for LUSC patients: